The effect of feed additives on biochemical and immunological blood parameters in growing pigs - Gordiienko, Iuliia; Gordiienko, Iuliia Anatoliivna; Hordiienko, Yuliia; Hordiienko, Yuliia Anatoliivna; Gordiienko, Iuliia A.; Gordiienko, Iu. A.; Гордієнко, Юлія Анатоліївна; Yanovska, О.; Yanovsky, O.; Yanovska, O. V.; Яновська, Оксана Віталіївна (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, 2025)
This study presents the results of biochemical and immunological indicators of clinically healthy young pigs of the Large White breed. The research was conducted against the background of expanding the basic diet with supplements having different mechanisms of action: the probiotics BioPlus 2B (based on Bacillus licheniformis СН 200 and Bacillus subtilis 201) and Bacell (Ruminococcus albus, Lactobacillus spp., Bacillus subtilis 8130 in composition), and a mixture of plant extracts Extract SV containing carvacrol, cinnamaldehyde, and capsaicin. Animals were randomly selected for the control group (Group 1), and for the experimental groups – according to the results of bacteriological studies of the intestinal microflora. Group 2 consisted of pigs with a reduced content of Escherichia coli, which consumed BioPlus 2B with the basic diet, Group 3 – pigs with a reduced content of Lactobacillus spp., which consumed Bacell, Group 4 – animals with a normal ratio of E. coli, bifidobacteria and lactobacteria. Blood samples were taken immediately after the distribution of pigs into groups (day 0) and on days 18 and 62. When using feed additives, an increase in the concentration of total protein in pigs was observed on day 62, alongside changes in the protein profile of animals that consumed BioPlus 2B – an increase in α1-globulins by 1.33 times (P ˂ 0.01), and Extract SV – β-globulins by 1.18 times (P ˂ 0.01), BUN and creatinine by 10 % (P ˂ 0.05), which indicated the absence of violations of the protein synthesis function of the liver. On day 18, we observed a significant increase in the concentration of IgG by 10 % in animals consuming Bacell, which may indicate a temporary immune-stimulating effect. The prevalence of Lactobacillus spp. and Bifidobacterium spp. in the intestine when consuming feed additives indicates a relationship between the structure of the microbiome and the biochemical and immunological indicators of the experimental pigs. The described approach to selecting feed additives allows us to achieve maximum efficiency and predict results in industrial pig farming, thereby optimizing the production cycle and increasing the profitability of the farm. В роботі наведені результати дослідження біохімічних та імунологічних показників клінічно здорового молодняку свиней великої білої породи на тлі додавання до основного раціону добавок із різними механізмами дії: пробіотиків BioPlus 2B на основі Bacillus licheniformis СН 200 та Bacillus subtilis 201 і Bacell із Ruminococcus albus, Lactobacillus spp., Bacillus subtilis 8130 у складі та суміші рослинних екстрактів Extract SV з карвакролом, циннамальдегідом та капсаїцином у складі. До контрольної групи (1-ша група) тварин обрали довільно, до дослідних груп – за результатами бактеріологічних досліджень мікрофлори кишківника. 2-гу групу становили свині зі зниженим вмістом Escherichia coli, які з основним раціоном споживали BioPlus 2B, 3-тя – свині зі зниженим вмістом Lactobacillus spp., які споживали Bacell, 4-та – тварини з нормальним співвідношенням кишкової палички, біфідо- та лактобактерій. Зразки крові одержували одразу після розподілення свиней по групах (0 доба) і на 18 та 62 добу. При застосуванні кормових добавок спостерігалось підвищення концентрації загального білка у свиней на 62 добу на тлі змін білкового профілю тварин, які споживали BioPlus 2B – збільшення α1-глобулінів у 1,33 рази (p ˂ 0,01), та Extract SV – β-глобулінів у 1,18 разів (p ˂ 0,01), BUN і креатиніну на 10 % (p ˂ 0,05), що вказувало на відсутність порушень білоксинтезувальної функції печінки. На 18 добу у тварин на тлі вживання Bacell відбувалось значуще підвищення концентрації Іg G на 10 %, що може свідчити про тимчасовий імуностимулювальний ефект. Превалювання Lactobacillus spp. і Bifidobacterium spp. у кишківнику при споживанні кормових добавок свідчить про наявність взаємозв’язку між структурою мікробіому, біохімічними та імунологічними показниками дослідних свиней. Описаний підхід при підборі кормових добавок дозволяє досягти максимальної ефективності і спрогнозувати результати в промисловому свинарстві, оптимізуючи виробничий цикл та підвищуючи рентабельність господарства.
Вплив кормових добавок на біохімічні та імунологічні показники крові свиней на вирощуванні
Гордієнко Юлія Анатоліївна https://orcid.org/0000-0003-0788-2176 Яновська Оксана Віталіївна https://orcid.org/0000-0003-1872-283Х
Keywords: biochemical blood parameters; біохімічні показники крові; growing pigs; свині на вирощуванні; gut microbiome; мікробіом кишківника; probiotics; пробіотики; phytobiotics; фітобіотики; immunity; імунітет